A research paper on the local metal industry capability to manufacture the indigenous Escalona_Esma 5.56mm Assault Rifle (EE 5.56mm AR) - Escalona, Herr K.; Cruz, Edison (Quezon City University of the Philippines Diliman, 2008)
National Self Reliance in defense and economy is a worldwide goal and form part and parcel of National power. To date the Philippines does not have these two main elements of national power. The defense establishment as an organization is one of the many economic opportunity a country has by locally providing for the its defense needs. Recognizing this potential, then President Ferdinand Marcos issues PD 415 otherwise known as the Self Reliant Defense Posture (SRDP) Program of the Philippine Government. The government went into military equipment research and Development activities. Many of them were a success to an extent but most were a failure. These projects engendered in-country production of our defense needs through partnerships with civilian establishments, and helped developed the local defense industry by maximizing the utilization and processing of indigenous materials and production capability of the country. During the last quarter of 2006, in an effort to help this national SRDP Program, a private Research and Development activity was successfully conducted. This group is made up of hobbyists, professionals, advocates, military and civilian leaders, and metal industry players. The project focused on the goal of having national self sufficiency in assault rifle. After a thorough laboratory testing and some field testing, it was recognized that the capital requirement to establish a traditional rifle line manufacturing facility is magnanimous. The group was compelled to find alternative method/s in manufacturing the indigenous rifle within accepted economic parameters with minimum capital. To do so, great historical economic paradigm were studied to set a benchmark in the production of the EE5.56mmAR. Adam Smith of the late 19th century, Japan's Economic Miracle of the last quarter of the 20th century, and the most recent, that of China's double digit economic growth mainly thru its manufacturing activities. Being a third world country, the country has a very limited financial capital to invest heavily into this indigenous rifle design. Moreover, being a archipelagic in territory, manufacturing activities are localized within the limitations of transportation. Emulating some of the good points of economies cited above and localizing the situation, the approach deemed appropriate for this national goal is that to consider greatly Michael Porter's Diamond of advantage paradigm. He conducted research on industry cluster and developed the Diamond of Advantage, Figure 14, a model that offers insights into industry clusters and competitiveness. Porter contends that nations develop a competitive advantage based on their firms' ability to continually innovate, and that economic vitality is a direct product of the competitiveness of local industries.
Following this industry Cluster, naturally, the next effort to follow should be to analyze the metals industry players individually and collectively thus, this project paper. This is the way to ascertain if the local metals industry has the technological capability to engage in the mass production of the indigenous rifle. For this research, the following research methods were utilized : a. Administered survey questionnaires to selected companies from the different metals and engineering sector that may join the project; b. Actual site visits to selected companies of the metals and engineering industry; c. Conducted focus group discussion with the different representatives of each metalworking sector; d. Conducted research on the industry studies from the Metals Industry Research and Development Center (MIRDC); and e. Manufactured seven (7) assault rifle units to assimilate production capability of the industry. The result of the five methods of research was encouraging on the researchers end as the primary designer of the rifle, as a student of this Course, and as an advocate of SRDP. The results are all showcasing the sufficient industrial strength and capability of the Filipino machine shops to manufacture the indigenous rifle design both to meet the local demand and the possible export as well. In order to support the industry cluster as a national strategy and to proceed with the EE5.56mmAR manufacturing from its present state, the following recommendations are deemed important if at all the country shall proceed with achieving this SRDP goal. For the mass production of the EE AR 5.56 the following strategies are recommended for consideration : For the Technical concerns : 1. Government metals industry related facility such as the MIRDC of the DOST, and military and Civilian Research and Development centers should be tapped. 2. Development of the necessary toolings required for the mass production of the rifle must be effected to achieve economy of scale. 3. Forging facility be established to produce some parts of the rifle. This facility may also be used in the production of other civilian metal machinery parts and components. 4. Inventory of discarded M16 rifles and spare parts in the AFP and PNP must be gathered, cannibalized and or refurbished. For the Administrative concerns : 1. All participating companies that will be joining the project must or should be ISO certified. This is necessary in the export of the rifle. 2. The government should have a proactive role in this by issuing to Companies that will be joining the project government permit to manufacture firearms or its components. 3. Defense Industry Association must be inclusive in outlook instead of exclusive. The defense establishment should encourage this. For the Legislative concerns : 1. Tax incentives must be applied for all imported raw materials/equipment/machinery that will be used in the manufacture of the rifle. This will reduce the cost significantly of the EE AR 5.56 both for domestic use and export. 2. Tax incentives/breaks/holidays may be given to the participating company during the initial years of their operation in connection with this project. 3. The government must protect the commercialization of the indigenous AR by taxing appropriately the imported assault rifles whether as a unit or as spare parts.
In partial fulfillment of the requirements in TM 299.2
Thesis
Keywords: Steel industry and trade; Escalona_Esma 5.56mm Assault Rifle (EE 5.56mm AR).